1984
DOI: 10.1093/bja/56.9.1009
|View full text |Cite
|
Sign up to set email alerts
|

Fetal-Neonatal Status Following Caesarean Section for Fetal Distress

Abstract: Fetal biochemical and neonatal clinical data were compiled in 126 emergency Caesarean sections performed for fetal distress. The choice of anaesthetic technique was determined by the wishes of the mother. General anaesthesia was administered to 71 parturients and regional analgesia to 55 (subarachnoid block 33, extension of extradural block 22). The aetiologies of fetal distress and the skin incision-delivery and uterine incision-delivery intervals were not significantly different between the two anaesthesia g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 9 publications
3
14
0
3
Order By: Relevance
“…The total spinal times for optimistic (fastest preparation + fastest onset), median (median preparation + median onset) and pessimistic (slowest preparation + slowest onset) were 3:31, 8:52 and 17:22, respectively. Our times are comparable to a clinical observational study by Kinsella et al who described a case series of 25 'rapid sequence spinals' and found the median (IQR [range]) time to prepare and perform the spinal was 2 (2-3 [1][2][3][4][5][6][7]) min and to develop a 'satisfactory' block was 4 (3-5 [2][3][4][5][6][7]) min. The optimistic time calculated in the same way was 3 min, and the pessimistic was 14 min.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The total spinal times for optimistic (fastest preparation + fastest onset), median (median preparation + median onset) and pessimistic (slowest preparation + slowest onset) were 3:31, 8:52 and 17:22, respectively. Our times are comparable to a clinical observational study by Kinsella et al who described a case series of 25 'rapid sequence spinals' and found the median (IQR [range]) time to prepare and perform the spinal was 2 (2-3 [1][2][3][4][5][6][7]) min and to develop a 'satisfactory' block was 4 (3-5 [2][3][4][5][6][7]) min. The optimistic time calculated in the same way was 3 min, and the pessimistic was 14 min.…”
Section: Discussionsupporting
confidence: 84%
“…In a UK survey, the median (IQR [range]) rate of use of general anaesthesia for category-1 caesarean section was 51% (29-80% [6-100%]) [4]. Marx et al found that spinal anaesthesia can be induced acceptably quickly for caesarean section for fetal distress [5]. However, they used a 22-G spinal needle which is significantly bigger than those in current use, and amethocaine which is also not commonly used in modern practice.…”
Section: Discussionmentioning
confidence: 99%
“…One minute Apgar score <7 were significantly better following regional block despite the presence of fetal distress. Similar finding were observed in other studies like Marx, G. [25,26]. There were no significant differences found in neonatal outcome between both techniques at five minutes in group 3.…”
Section: Discussionsupporting
confidence: 92%
“…En av årsakene til denne endringen er at man anser regionalanestesi for å vaere en tryggere anestesiteknikk enn generell anestesi både for mor og foster/nyfødt (3)(4)(5). Risiko for maternell mortalitet og morbiditet reduseres og barna har høyere apgarskår dersom regionalanestesi benyttes (4,5). Anestesilegen skal avgjøre valg av anestesimetode i samarbeid med den føden-de og fødselslegen.…”
Section: Sammendragunclassified